2023
DOI: 10.1039/d2fo03992c
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic selenium nanoparticles alleviate intestinal epithelial barrier injury by regulating mitochondria–lysosome crosstalk

Abstract: SeNPs can regulate mitochondrial and lysosomal crosstalk through the TBC1D15/Fis1/Rab7-mediated signaling pathway and maintain cell homeostasis, and further effectively alleviate intestinal epithelial barrier dysfunction in IPEC-J2 cells exposed to LPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Similarly, upregulation of miR-182 in I/R mice leading to a significant reduction in autophagosomes has also found morphological evidence observed by TEM[ 44 ]. Studies have found that selenium nanoparticles can effectively alleviate intestinal epithelial barrier damage by inhibiting autophagy mediated by the TBC1D15/Rab7 signaling pathway[ 45 ]. In contrast to the above studies, activation of the AMPK/ SIRT1-autophagy pathway alleviated intestinal I/R injury[ 46 , 47 ].…”
Section: Autophagy and Gi Diseasesmentioning
confidence: 99%
“…Similarly, upregulation of miR-182 in I/R mice leading to a significant reduction in autophagosomes has also found morphological evidence observed by TEM[ 44 ]. Studies have found that selenium nanoparticles can effectively alleviate intestinal epithelial barrier damage by inhibiting autophagy mediated by the TBC1D15/Rab7 signaling pathway[ 45 ]. In contrast to the above studies, activation of the AMPK/ SIRT1-autophagy pathway alleviated intestinal I/R injury[ 46 , 47 ].…”
Section: Autophagy and Gi Diseasesmentioning
confidence: 99%